DIVERSITY AND VERTICAL DISTRIBUTION OF VASCULAR EPIPHYTES ON A MALAYSIAN MANGROVE ISLAND - Shahrudin Rohani; Fei Lin Lee; Abdul Shukor Yusoff (BIOTROPIA, 2020)
Many studies have attempted to explain the diversity and abundance of epiphytic plants in major ecosystems worldwide. However, investigations on the abundance of epiphytic plants in mangroves have remained rare. The aim of this research was to study the diversity and vertical distribution of vascular epiphytes in a mangrove forest in Peninsular Malaysia. Sampling was conducted over a 0.1-hectare plot on Pulau Telaga Tujuh, a mangrove island in Terengganu, Malaysia. Trees with vascular epiphytes were divided into three strata: basal, trunk, and canopy. The vascular epiphytes were identified, and the number of individuals in each stratum was recorded. In total, eight species of vascular epiphytes from six genera and four families were recorded. Pulau Telaga Tujuh mangrove forest exhibited a relatively low diversity of vascular epiphytes (H' = 1.43). The dominance of Hydnophytum formicarium significantly contributed to the diversity of vascular epiphytes in this forest. The highest abundance of epiphytes was observed on the trunks of the host trees. The vertical distribution pattern observed in this study is associated with the adaptation of epiphytic plants to stresses in the mangrove ecosystem, particularly drought and salt spray. Pulau Telaga Tujuh had a high density of vascular epiphytes but lower diversity compared with other ecosystems.